anonymous
  • anonymous
Evaluate and tell if it is extraneous or not. x^2-6x+13=0
Algebra
chestercat
  • chestercat
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
anonymous
  • anonymous
Step 1 : Raise x to the 2nd power
anonymous
  • anonymous
factor?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
this is the Equation at the end of step 1 : (x2 - 6x) + 13 = 0
anonymous
  • anonymous
Step 2 : Simplify x2-6x + 13
anonymous
  • anonymous
3+ or - 2i
anonymous
  • anonymous
Equation at the end of step 2 : x2 - 6x + 13 = 0
anonymous
  • anonymous
ok:)
anonymous
  • anonymous
so what would the answer be? bc i factored it
anonymous
  • anonymous
Simplifying x2 + 6x + 13 = 0
anonymous
  • anonymous
Reorder the terms: 13 + 6x + x2 = 0 Solving 13 + 6x + x2 = 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '-13' to each side of the equation. 13 + 6x + -13 + x2 = 0 + -13 Reorder the terms: 13 + -13 + 6x + x2 = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 6x + x2 = 0 + -13 6x + x2 = 0 + -13 Combine like terms: 0 + -13 = -13 6x + x2 = -13 The x term is 6x. Take half its coefficient (3). Square it (9) and add it to both sides. Add '9' to each side of the equation. 6x + 9 + x2 = -13 + 9 Reorder the terms: 9 + 6x + x2 = -13 + 9 Combine like terms: -13 + 9 = -4 9 + 6x + x2 = -4 Factor a perfect square on the left side: (x + 3)(x + 3) = -4 Can't calculate square root of the right side. The solution to this equation could not be determined.

Looking for something else?

Not the answer you are looking for? Search for more explanations.